Aerothermodynamics Response of Hypersonic Flow over a Blunt Cone under Distributed Rough Element. Issue 5 (January 2021) - Tang, Xiaojun; Zhang, He; Yu, Juan; Tang, Caiyan; Li, Haixia
Abstract: A direct numerical simulation method is used to simulate the hypersonic blunt cone flow field under the condition of smooth wall and distributed rough element. The effects of smooth wall and distributed rough element on hypersonic flow field and wall are compared and analyzed, and the aerothermodynamic response characteristics of hypersonic flow field to distributed rough element are studied. The results show that the effect of the distributed rough element on the hypersonic flow field and boundary layer is significantly higher than that of the smooth wall. The friction coefficient of the wall is directly proportional to the velocity gradient of the flow direction in the boundary layer, while the velocity gradient of the flow direction is inversely proportional to the thickness of the boundary layer. The heat flux density of the wall increases at the front edge of the rough element to promote the heating, and decreases at the second half of the rough element to inhibit the heating.